Educaçao de tempo integral no Brasil : história, desafios e perpsectivas - Cella, Rosenei (2010)
This research presented and discussed the main Brazilian experiences in education full time, which marked the educational history of our country and have served as basis for the realization of new school models. Among the most consistent historical experience is the School-Park Bahia, created by educator Teixeira in the 1950s, but also CIEPs Rio de Janeiro, government Brizola. Are also listed current public policies, targeted at financing the expansion of the school in Brazilian public schools, especially FUNDEB and More Education Program. The National Education Plan and LDB 9394/96 advocate the gradual expansion of the school as a target of investment in Brazilian public education. The debate over the quality of education also permeates this work, as investments in education are only justified when the objective is to ensure effective learning and improvement of education, educating individuals to build a less unequal society, a process that should begin in school, providing opportunities for conditions of full development of individuals. Large-scale tests such as the Brazil race, which serves as the basis for the composition of IDEB, as well as PISA, bring evidence that our country still needs much research and investment in education, since the guarantee of learning does not rule at school. Municipal education leaders from 25 Brazilian states were heard about the possibility of deploying full-time education in the municipalities where they operate and the variables that complicate the process of expanding the school day. The responses of the questionnaire given to municipal leaders show some indications about the difficulties faced by municipalities that wish to implement a full-time education in their schools. Based on the considerations of municipal leaders from education, it is possible to say that most of them understand that education is a full-time alternative pedagogically valuable, but there are still many barriers to their deployment, as the fiscal responsibility of the municipal limits certain investments and hires